Evaluation of the Chetomin effect on histopathological features in a murine acute spinal cord injury model - Carlos César Bravo-Reyna; Vladimir Miranda-Galván; Gervith Reyes-Soto; R. Vicuña; Jorge Alanis-Mendizabal; Manuel Escobar-Valderrama; David Arango; Claudia J. Bautista; Victoria Ramírez; Gonzalo Torres-Villalobos (World Neurosurgery: X)
Background: Several research studies have been focused on improving the treatment and prognosis of acute spinal cord injury, as part of this initiative we investigated the use of Chetomin to reduce the inflammatory response in this pathology. Methods: An experimental, prospective, cross-sectional study was performed using 42 Wistar rats where we analyzed the effect of Chetomin compared to methylprednisolone administered 1 and 8 h after the spinal cord injury in a murine model. Results: Chetomin administration 8h post-injury decreased IL-6 and VEGF expression; and, and its administration 1h post-injury decreased NF-kB expression. Conclusions: Chetomin has anti-inflammatory effects in acute spinal cord injury, whether these effects are observable with other proinflammatory markers should be investigated.